Structures Congress 2018 : buildings and disaster management : selected papers from the Structures Congress 2018, April 19-21, 2018, Forth Worth, Texas - Soules, J. G. (American Society of Civil Engineers, 2018)
This collection contains 41 peer-reviewed papers on buildings and disaster management presented at the Structures Congress 2018, held in Fort Worth, Texas, April 19-21, 2018.